Systematic revue of the tools for multiprofessional primary care teams assessment - François, P; Cardaci, C; Lopez-Ruiz, C; Boussat, B; Marchand, O (Revue d'épidémiologie et de santé publique, 2017)
Multiprofessionnal teams in primary care are developing in many countries including France. These groups appear very heterogeneous regarding the level of integration and interprofessional cooperation. A systematic review of the literature was performed to screen the instruments which assess the organizational development of primary care groups. Scientific literature was searched in the Pubmed database, gray literature was searched for on the Internet. The documents were selected by two independent investigators. The collected data included information on assessment instruments: origin, content, method of use, and validation process. Sixty-five documents involving 16 assessment instruments were selected for the study. Twelve instruments have been developed in North America and 4 in Europe. Four instruments were evaluation questionnaires, 4 accreditation tools and 8 were maturity matrices. The maturity matrices were structured by levels of organizational development. Their use were effected by an individual self-assessment of each professional and then by consensus of the group in the presence of an external facilitator. The questionnaire and accreditation tools have organizations and use patterns variable. The number of questions ranged from 25 to 200 with a median of 80. The instruments were organized into 4 to 16 dimensions with a median of 7. Six common themes were identified: practice and staff management, quality development, data patient management, interprofessional cooperation, accessibility and continuity of care, and formation. The validation process of tools were variable and often incomplete. The set of assessment tools for primary care group is heterogeneous in purpose, content and mode of use. However, common themes were found for all tools. An evaluation questionnaire, in French, would be useful to monitor over time and evaluate the organizational development of centers and health houses in France.